A Study on Acanthocephala and Some Nematodes in Chub Mackerel Scomber Japonicas on The Coast of Tripoli City, Libya (Libyan Journal of Ecological & Environmental Sciences and Technology, 2022)
The current study examined the effects of Echinorhynchus gadi  , and Anisakis larva on Chub Mackerel (Scomber japonicas ) This study was carried out from February to April 2018, in Tripoli- Libya using 50 fish, fish were collected from market fish in Tripoli city, Chub Mackerel (Scomber japonicas ). The results indicate that the level of infection of 60% of all examined fish, Fish were infected with intestinal parasitic worms. Two types of worms were identified through the examination, Echinorhynchus gadi and Anisakis larva, the proportion incidence rate of these parasites was 53.3% and 46.6% respectively.In addition, the morphological characteristics of each parasite were identified.
Keywords: Chub Mackerel fish; Intestinal parasites; nematodes. Tripoli-Libya Acanthocephala; nematodes; Acanthocephala; Tripoli-; Libya